Perspective: Soybeans Can Help Address the Caloric and Protein Needs of a Growing Global Population - Messina, Mark (Frontiers in Nutrition, 2022)
Feeding a growing global population with projected rising socioeconomic status will require additional sources of calories and especially protein. These sources need to align with the Sustainable Development Goals established by the Food and Agriculture Organization of the United Nations. The soybean is uniquely positioned to meet this challenge based on the following criteria: 1) Global soybean production exceeds by ~4 times the production of all pulses combined 2) Soybeans are higher in protein than other legumes and soy protein quality is similar to animal protein quality 3) Soybeans are an excellent source of healthy fat, including both essential fatty acids 4) Soybeans, like other legumes, symbiotically fix atmospheric nitrogen thereby reducing the need for fertilizer inputs 5) Greenhouse gas emissions per unit protein are lower than for nearly all other foods 6) Soybeans, like other legumes, are also recognized as an affordable food that can be incorporated into diverse diets regardless of economic standing and 7) The range of foods produced from soybeans constitutes an important position in historic and contemporary cuisines, cultures and emerging consumer trends for plant-based protein. Although most soybeans are currently used for animal feed, soybean use is dictated by consumer demand. Therefore, soybeans are well positioned to meet future global needs for energy and protein. Armed with this knowledge, health professionals can feel justified in encouraging greater consumption of soyfoods for both personal and planetary reasons.